Kemampuan Daya Tangkap Anak dalam Pembelajaran Kelas V MIS Al Mukhlisin Kabupaten Deli Serdang - Dedek Mauliddiani; Dirja Hasibuan; Hotni Sari Harahap (Journal on Education, 2023)
From the results of interviews and research observations, it is known that in class V at the MIS AL-Mukhlisin Deli Serdang school there are several children who are included in the category of children who have strong grasping abilities in absorbing learning, and there are also several children who have weak comprehension in absorbing learning. through the teaching and learning process in the classroom. From the observation results it is also seen that there is no learning media and learning curriculum for students, especially for students who have weak comprehension, but are equated with students who have strong comprehension or children who are active in other learning. Based on the results of interviews and observations, it is known that there is no difference between learning media and the learning curriculum for students who have strong comprehension abilities or children who are active in other learners and students who have weak comprehension abilities or are slow learners. In the midst of efforts to increase students' interest in learning, in fact there are also supporting and inhibiting factors, namely: 1) supporting factors such as adequate facilities and infrastructure, the support of teachers and educators. 2) the inhibiting factors are the lack of enthusiasm for student learning, family and social environmental factors, and socio-economic factors of the student's family.